THE THE EFFECT OF GOOD CORPORATE GOVERNANCE ON STOCK PRICE THROUGH CORPORATE VALUE IN THE FINANCIAL SERVICES CLUSTER OF INDONESIAN BUMN COMPANIES - Lily Karlina Nasution; Mayang Murni; Ika Sari Dewi (SEAN Institute, 2023)
A good financial services company can be assessed by the quality of the performance of its issuers as assessed by good corporate governance and the value of its profitability. Thepurpose of this study is to identify the effect of good corporate governance, which is proxied by institutional ownership, managerial ownership, the audit committee, and the board of commissioners, and profitability, which is proxied by return on assets, on share prices in BUMN companies in the financial services cluster for 2017–2021. The data used is secondary data from the financial statements of the BUMN companies in the financial services cluster and is analyzed using multiple linear regressions. The results of the study show that simultaneously, the institutional ownership, managerial ownership, audit committee, board of commissioners, and return on assets variables have a significant effect on stock prices. Meanwhile, only the audit committee variable partially has no effect on the stock price, while the institutional ownership, managerial ownership, board of commissioners, and profitability variables have a significant effect on the stock price.